FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK TAX AVOIDANCE PADA PERUSAHAAN MUTINASIONAL DI INDONESIA - Kemala Octisari, Sully; Nia Iskandar, Christiana; Wijaya, Minadi; Lestari, Puji (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Taxes as mandatory contributions that force cause multinational companies to do tax avoidance. The study aims to determine the influence of variable board gender diversity, leverage, and profitability on tax avoidance practices on multinational corporations. The data used is secondary data, while the method used is regression analysis of panel data with Eviews 10 to obtain a comprehensive picture of one variable with another variable. The sample in the study consisted of 44 multinational companies registered with the IDX during the period 2016- 2019 using purposive sampling on sampling methods. The results of this study showed that board gender diversity had no significant effect on tax avoidance practices. Leverage has a positive and significant effect on tax avoidance practices. Profitability negatively and significantly affects tax avoidance practices.